Chimeric Antigen Receptor T-Cells for the Treatment of B-Cell Acute Lymphoblastic Leukemia - Tomuleasa, Ciprian; Fuji, Shigeo; Berce, Cristian; Onaciu, Anca; Chira, Sergiu; Petrushev, Bobe; Micu, Wilhelm-Thomas; Moisoiu, Vlad; Osan, Ciprian; Constantinescu, Catalin; Pasca, Sergiu; Jurj, Ancuta; et al. (Frontiers in Immunology, 2018)
Chimeric antigen receptor (CAR) T cell technology has seen a rapid development over the last decade, mostly due to the potential that these cells may have in treating malignant diseases. It is a generally accepted principle that very few therapeutic compounds deliver a clinical response without treatment-related toxicity, and studies have shown that CAR T-cells are not an exception to this rule. While large multinational drug companies are currently investigating the potential role of CAR T cells in hematological oncology, the potential of such cellular therapies are being recognized worldwide as they are expected to expand in the patient in order to support the establishment of the immune memory, provide a continuous surveillance in order to prevent and/or treat a relapse and keep the targeted malignant cell subpopulation in check. In the current paper, we present the possible advantages of using CAR T cells in treating acute lymphoblastic leukemia, presenting the technology as well as the current knowledge in their preclinical and early clinical trial use. Thus, the manuscript first presents the main present day knowledge on the standard-of-care for acute lymphoblastic leukemia. Afterwards, current knowledge is presented about the use of CAR T cells in cancer immunotherapy, describing their design, the molecular constructs and the preclinical data on murine models in order to properly explain the background for their clinical use. Last, but certainly not least, the paper presents the use of CAR T cells for the immunotherapy of B-cell acute lymphoblastic leukemia, describing both their potential clinical advantages, as well as the possible side-effects.